Web crippling capacities of fastened aluminium lipped channel sections subjected to one-flange loading conditions. (October 2021) - Alsanat, Husam; Gunalan, Shanmuganathan; Poologanathan, Keerthan; Guan, Hong
Highlights: Experimental and numerical web crippling investigations of roll-formed aluminium lipped channel sections were performed. One-flange loading conditions with fastened flanges were considered. Current design equations based on Australian and European aluminium specifications were generally found to be unsafe. Modified design guidelines were proposed against a wide range of parametric data. Abstract: Recently, a new generation of roll-formed aluminium sections have been produced by BlueScope Permalite Australia and utilized in structural systems. However, limited research has been conducted to investigate their buckling instabilities including web crippling failure. The empirical nature of the current design guidelines may also lead to inaccurate estimation to their web crippling capacities. Therefore, this study aims to investigate the web crippling behaviour of and the design considerations for roll-formed aluminium lipped channel (ALC) sections using a combination of experimental study and finite element analysis (FEA). In total, 40 ALC specimens were tested under one-flange loading conditions with flanges being restrained to the supports (Fastened). Non-linear finite element models were also developed and validated against the experiments. An extensive parametric study was subsequently conducted to extend the range of geometrical dimensions and aluminium alloy grades of ALC sections. Further, the applicability and accuracy of the design rules given in the American, Australian, and European specifications were assessed. It was found that most of these guidelines yield either unconservative or over-conservative predictions of the ultimate web crippling capacities, and hence suitable modifications were proposed. Predictions due to the modified design rules showed a good agreement with both experimental and numerical results, and are hence recommended to be incorporated in relevant aluminium standards.